Virtual Reality: Saving Tourism in South Africa? - Victoria-Ann Verkerk (African Journal of Hospitality, Tourism and Leisure, 2022)
At the end of 2019, a new crisis emerged in the world - COVID-19 - which literally devastated the tourism industry worldwide. In order to try to minimise the spread of COVID-19, the government implemented a strict national lockdown, but this unfortunately had a negative impact on many sectors within the tourism industry. In the light of this, many scholars argued that technology such as virtual reality (VR), would contribute to the recovery of tourism. This article considers this phenomenon by filling a gap in the literature regarding the role of VR in the tourism industry in the global South by focusing on South Africa. The key question that arises, namely can VR save tourism in South Africa in the wake of COVID-19? To address this question, the study uses three methodological approaches: case studies, a conceptual research method and open-ended interviews. The results from the study showed that VR offers tourism numerous benefits, but at the same time poses a threat to the industry. Despite this, the study concludes that VR cannot save the tourism industry in South Africa currently as it faces certain critical obstacles in this context.